Effects of rainfall exclusion on soil fungi in a boreal forest landscape - Koelemeijer, Irena A.; Castaño, Carles; Clemmensen, Karina E.; Ehrlén, Johan; De Frenne, Pieter; Jönsson, Mari; Hylander, Kristoffer (Elsevier, 2025)
Due to climate change, droughts are increasingly frequent and intense. Yet, their impact on boreal forest fungal communities remains unclear, especially across different fungal functional and taxonomic groups. We induced an experimental rainfall exclusion for 45 summer days, using a paired design of 1 × 1 m treatment and control plots replicated in 25 sites in a boreal forest landscape in Sweden. Immediately after the experiment, we assessed the effects on soil fungal biomass, community composition and, after 2 months, sporocarp production. We did not detect significant effects of the rainfall exclusion on soil fungal biomass, but the fungal community composition was affected. In the rainfall exclusion plots, richness of ectomycorrhizal species with extensive extramatrical mycelia and saprotrophic basidiomycetes was reduced, while richness of ascomycetes was not affected. Sporocarp production of both saprotrophic and ectomycorrhizal fungi was reduced. The clear effects of a small-scale rainfall exclusion demonstrated in our study suggest that belowground fungal communities in boreal forests may be vulnerable to drought.
Keywords: fungal community; global change ecology; Ectomycorrhizal; Saprotrophic; drought; forests; mycelial biomass; Sporocarp; extramatrical mycelial exploration